Pengukuran Pengalaman Pengguna Aplikasi Platform Pembelajaran dan Konferensi Video Menggunakan Framework UEQ+ - Angela Angela; Fandi Halim; Chatrine Sylvia (STMIK Budi Darma, 2022)
This study aims to measure and evaluate the user experience of the Microsoft Teams application as a learning and video conferencing platform using the UEQ+ framework, which is the development of the UEQ method. Through the UEQ+ framework, questionnaires can be designed by customizing user experience variables according to the application to be measured, thus the research results are expected to be more accurate and relevant. The scale of user experience measured in this questionnaire includes: efficiency, perspicuity, dependability, trust, usefulness, intuitive use, trustworthiness of content, quality of content, and clarity. After the questionnaires were distributed, 149 data were obtained which could be processed using data processing tools which being provided by UEQ+ called Data Analysis Tools. In conclusion, respondents have positive impression of Microsoft Teams as a video conferencing application and learning platform. The most important scale that represents the quality of Microsoft Teams is usefulness, clarity, trustworthiness of content, and quality of content.